Research on the use of Thyme as a Prophylactic Alternative in Gastrointestinal Disorders in Cattle - Adina-Mirela Ariton; Silviu-Ionuț Borș; Andra-Sabina Neculai-Văleanu; Ioana Poroșnicu; Vasile Vintilă (Scientific Papers Animal Science and Biotechnologies)
Thyme is a plant from the Mediterranean region, which belongs to the family Lamiaceae, used over time in the treatment of respiratory ailments, digestive ailments, and other diseases. This study presents the prophylactic and therapeutic properties of thyme extract in relation to certain gastrointestinal disorders in cattle. Early-life intestinal disorders in cattle are linked to a number of long-term effects, including a reduction in the severity of both pathogenic and non-pathogenic diarrhoea, a slowdown in growth, and a decrease in milk production during the first lactation, all of which result in significant financial losses. Because of its high concentration of thymol and carvacrol, which have exceptional antibacterial, antioxidant, and anti-inflammatory properties, thyme is used in both conventional medicine and phytopharmaceutical preparations. Therefore, the purpose of this review is to provide current information on the role of thyme in the homeopathic treatment of gastrointestinal disorders in dairy cattle.